Myocardial strain parameters and autonomic balance in various variants of the postinfarction course in patients receiving high-dose atorvastatin therapy - V. E. Oleinikov; A. V. Golubeva; Yu. A. Barmenkova; A. V. Kulyutsin; N. V. Burko; M. V. Lukyanova; N. A. Donetskaya (Российский кардиологический журнал, 2023)
Aim. To study parameters of left ventricular (LV) strain and heart rate variability (HRV) in patients with ST-segment elevation myocardial infarction (STEMI) in various variants of postinfarction receiving high-dose atorvastatin therapy.Material and methods. The study included 96 patients with STEMI. All patients underwent two-dimensional speckle tracking echocardiography and 24-hour electrocardiographic monitoring with HRV analysis. The included individuals were divided into groups without pathological LV remodeling (R (-), n=57) and with pathological post-infarction LV remodeling (R (+), n=39), the criterion for which was an increase in end-diastolic and/or end-systolic volume >20% and >15%, respectively. Further, depending on the achievement of target low-density lipoprotein cholesterol (LDL-C) (1,5 mmol/l and/or a decrease of more than 50%), the following subgroups were identified: 17 (43,6%) people, who reached target LDL-C levels (group 1), 22 (56,4%) patients, who did not reach target LDL-C levels (group 2). Similar subgroups were identified in the R (-) group as follows: 28 (49,1%) people, who reached target LDL-C levels (group 3) and 29 (50,9%) people, who did not reach target LDL-C levels (group 4).Results. Starting from the 12th week of follow-up, worsening of global longitudinal (GLS), circumferential (GCS), and radial (GRS) strain (p<0,01) was registered in group 2. In group 1, worsening of these parameters was registered only by the 48th week (p<0,01). In group 3, an increase in GLS was revealed by the 48th week (p=0,001), GCS and GRS — by the 12th week (p<0,05). In group 4, favorable changes were observed only in GLS and GCS by the 48th week (p<0,01). A significant change in HRV parameters was observed in group 3. By the 48th week, there was an increase in temporal indicators (SDNN, SDNNi, SDANN, RMSSD, pNN50) (p<0,0001) and total spectrum power (p=0,0001) due to an increase in all frequency indicators (p<0,001), while the index of autonomic balance L/H decreased by 33% (p=0,002). In group 4, only SDNN, SDANN and pNN50 (p<0,05), as well as the total spectrum power (p=0,001) increased, but no change in frequencies. According to intergroup analysis in the acute period of STEMI, group 4 patients had higher HRV than in group 3 (p<0,05).Conclusion. High-dose atorvastatin therapy improves LV strain characteristics and autonomic balance during the rehabilitation period after STEMI.